Justiça restaurativa e ato infracional: representações e práticas no judiciário de Campinas - SP - Chinen, Juliana Kobata (2017)
Restorative justice proposes a consensual administration of conflicts emphasizing the victim's harm, the responsibility of the perpetrator, and the needs of those involved in the conflict. The model is based on dialogue, respect and empowerment of the parties directly and indirectly involved. The present research aimed to reflect on the facilitators and complicating factors of the adoption of restorative justice by the traditional court system, focusing on the experience developed in the Child and Youth Court of Campinas since 2007. Besides the introduction and a chapter dedicated to methodological notes, the research was structured in three more chapters, starting with theoretical assumptions about restorative justice and its rapprochement towards juvenile justice in the Brazilian context. Next, the empirical field observed in the Campinas justice system was presented, addressing the history of the program implementation, its structure and its operation, and quantitative and qualitative data of the last two years. Priority was given to a qualitative approach to the case study, with interviews regarding the actors involved in the project, follow-up visits (pre-circles and restorative circles) and collection of statistical data on the restorative processes in Campinas. Finally, it was promoted discussions articulating the theory of restorative justice with the results of the immersions in the field, exploring the merits and critical factors of a program developed in the justice system, highlighting the following themes: (a) institutional visibility and structure; (b) the discourses and roles of institutional actors; (c) the symbolism of authority; (d) accountability and responses to the conflict; (e) selection of cases, increased social control and access to justice; and (f) the alternative or complementary role of restorative justice in regards to the justice system. The results of the study were in compliance with previous researches in the sense that, despite its transformative potential, the model has encountered several difficulties to be effectively developed, acting more as a reinforcement to the existing justice system than as a real alternative, considering a broader purpose of criminal policy. It was concluded that, while restorative justice plays an important role in qualifying a response to conflict, it should not be limited in its performance, at the risk of losing its critical power to oppose the current system.